Kajian Teoritis Penentuan Sudut Kemiringan Optimal Kolektor Surya Studi Kasus: Mataram - Nusa Tenggara Barat - Nanang Apriandi; Yusuf Dewantoro Herlambang; Totok Prasetyo; Margana Margana; Komang Metty Trisna Negara; Rani Raharjanti (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2023)
The performance of solar energy based apparatus in various locations is inseparable from the determination of the orientation direction and tilt angle. This study aims to determine an optimal tilt angle in Mataram city area. Photovoltaic Geographical Information System from European Commission (online) was used as the database to obtain global radiation and monthly average diffusion radiation on the horizontal surface with locus coordinates at Latitude/Longitude: -8.583°/116,107° South Latitude. That data was then processed mathematically using Microsoft Excel software. As the result, for the application of solar-based apparatus with a fixed structural configuration throughout the year, the optimal tilt angle (β) was 15° with the orientation facing north, and it was estimated that total solar radiation received throughout the year on average was 115,195 MJ/m2.